Compatibility of luxury and the concept of simply living - Soukupová, Barbora (2010)
Is luxury consumption incompatible with simple living? ... or not? For most of the people the question and the answer are obvious. On the first sight, it seems that there is no compatibility at all. How can luxury that is often connected and used as a synonym for opulence, excessive useless things and so on be even placed in one sentence with such a frugal concept as simple living? The purpose of this thesis is to define the framework and the issues that arise when putting the two concepts together. The findings of the thesis can be treated in deeper research that can follow and be inspired by this thesis. In order to prove and explain the analytical part, the findings are applied on real life examples. The theoretical part defines what luxury is, what its specific attributes are and why it stands apart from the "traditional" marketing approach. What is more, the impact of internalization and globalization on the luxury products and services is particular and cannot be treated in the same manner as for the mass consumption brands. The second analytical part treats the concept of simple living, the common misunderstandings and the philosophy of the concept. The two concepts are then put together in order to search for some for the points in common and the incompatibilities. The last chapter is dedicated to a practical illustration of the theory stated. Five star spa hotel and forest retreat Chateau Mcely is used as an example of luxury meeting simple living in some areas. The hotel is briefly introduced starting with the history of the building and then the modern history of the today's hotel after it was acquired by the actual owners, Inéz and James Cusumano. The mission statement and the principal idea of the project are detailed same as is the marketing mix of Chateau Mcely. And finally, the sustainability and ways of creating it are presented in order to underline the symbiosis of luxurious hotel and simple living, at least in some domains.